2023
DOI: 10.3390/epidemiologia4020012
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Surveillance Bias in Cancer

Abstract: Surveillance bias arises when differences in the frequency of a condition are due to changes in the modality of detection rather than to a difference in the actual risk of the condition. This bias hampers the surveillance of scrutiny-dependent cancers, leading to misinterpretations of cancer trends, risk factor identification, and, consequently, to the wrong public health actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This was also observed in our cohort, where patients with GD underwent more screening tests for cancer compared to controls. A higher frequency of screening tests can lead to a higher probability of detecting cancers, and this higher probability can be misinterpreted as a higher disease risk [13]. Undergoing more skin screen tests probably increased the likelihood of being diagnosed with skin cancer, mainly NMSC [14].…”
Section: Discussionmentioning
confidence: 99%
“…This was also observed in our cohort, where patients with GD underwent more screening tests for cancer compared to controls. A higher frequency of screening tests can lead to a higher probability of detecting cancers, and this higher probability can be misinterpreted as a higher disease risk [13]. Undergoing more skin screen tests probably increased the likelihood of being diagnosed with skin cancer, mainly NMSC [14].…”
Section: Discussionmentioning
confidence: 99%
“…from DSM-IV to DSM-V and ICD-10 to ICD-11), 46,47 or clinical guidelines, which may alter sampling over time and bias GD prevalence estimates (see "chronology bias" or "surveillance bias"). 48,49 The authors fail to demonstrate that the observed increase is either unexpected or of concern, yet the assumption of both underpins the Cass Review and its commissioning. Regarding the co-occurrence of ASD and GD, the authors conclude that this has increased, without appropriate statistical tests (e.g., time trend analysis) 50 or consideration of changes in the visibility and diagnosis of ASD, despite also warning of large confidence intervals.…”
Section: The Primary Researchmentioning
confidence: 99%